Profile of non-suicidal self-injury in adolescents: interface with impulsiveness and loneliness - Renata Pires de Oliveira Costa; Anna Lara Rocha Pinheiro Peixoto; Cirllainy Clécia Alves Lucas; Débora Nicácio Falcão; Jennifer Thayse da Silva Farias; Luiz Felipe Pereira Viana; Manuela Andrade de Alencar Pereira; Maria Letícia Barboza Sandes; Thomas Bernardes Lopes; Kristiana Cerqueira Mousinho; Euclides Maurício Trindade-Filho (Elsevier, 2021)
Objective: Comprehend the profile and prevalence of non-suicidal self-injury (NSSI) in adolescents and its association with impulsiveness and loneliness. Methods: Cross-sectional study carried out in 2017 in Maceió-Alagoas, Northeast Brazil, in the households of 505 adolescents aged 12-17 years, using a sample stratified and randomized by gender and neighborhood. The following instruments were used: a sociodemographic questionnaire, Brazilian version of Functional Assessment of Self-Mutilation (FASM), the Brazilian Barratt Impulsiveness Scale (BIS-11), and the Brazilian Loneliness Scale (UCLA-BR). Results: A prevalence of 6.53% was found for non-suicidal self-injury disorder (DSM-5). Significant differences ( p ≤ 0.05) were observed regarding: the most frequently used forms of NSSI were the items "cut oneself" and "scratch oneself"; engaging in three or more different forms of self-injurious behavior (66.67%) and, reporting as reasons, "to relieve feelings of emptiness or indifference" and "to stop bad feelings/sensations." Significance was also related to the sociodemographic profile: 72.73% were females and 63.54% had family income below one minimum wage. Individuals with self-injurious behavior also had higher impulsiveness and loneliness scores (p ≤ 0.05). Conclusions: The study identified a direct association between NSSI and impulsiveness and loneliness among adolescents, being more prevalent in females and in young individuals with socioeconomic vulnerability. The data provide support for improving public health policies, aimed at education, prevention, and treatment of adolescents with NSSI.